Links between Study Outcomes and Learning Tools: Theoretical Background - Žibėnienė, Gintautė (Pedagogika, 2016)
The article was prepared on the following conceptual theoretical provisions: Study outcomes is the basic part of a study programme when planning the content of studies, organizing study process, evaluation criteria of students‘ achievements, means and aids (Adam, 2004, 2007, 2008); Study outcome is the main feature of teaching / study programmes; the fundamental element of a teaching / study programme is study outcomes, denoting intended student’s knowledge, abilities and determining substantiation of the remaining elements of the study content (Laužackas, 2008; Pukelis, 2009); Interrelation of quality study process and evaluation of study outcomes with curriculum theory, where study programme is a constantly changing and self-renewing system, with all structural parts directed towards study aims, study outcomes (Kerr, 1967; Laužackas, 2000, 2008; Tyler, 1949; Žibėnienė, 2014); Provisions of European higher education space creation, formulated during Bologna process by ministers of education of participating countries in meetings, documents of European Commission and its authorized institutions (BOLOGNA beyond 2010, Communiqué of the Conference of European Ministers Responsible for Higher Education, Leuven and Louvain-la-Neuve, 2009; Standards and Guidelines for Quality Assurance in the European Higher Education Area, 2009); study outcomes interface with taxonomy methodology (Kennedy, Ryan & Hyland, 2009; Aligning with Outcomes Assessment, 2012) and study methods and evaluation methods (Žibėnienė, 2014). Lithuania applies a study content designing model directed towards study aims and outcomes, dominating in European countries (R. W. Tyler), when a study programme is designed by setting study aims, study outcomes and foreseeing their further division according to the logical base and subject outcomes. Therefore responsibly formulated study outcomes of a study programme is not only a prerequisite for study quality – their formulation shows a clear direction for all participants of the study process in planning and carrying out evaluation of students’ achievements, directed towards evaluation of study outcomes.